Analisis Naskah Drama Year Ten Thousandth Karya Fajri Syamsirani Dengan Unsur Dekonstruksi - Bahonie, Siti Khadijah Robert; Hefni, Asnan; Indrahastuti, Tri (Universitas Mulawarman, 2019)
The main aim to make a drama script entitled “Year Ten Thousandth” by Fajri Syamsirani as a research with intend of examining the facts of the story and dismantling the script into elements of deconstruction. This study uses a qualitative method, by deciphering word and symbols full of meaning. Describe the data based on the facts of the story, including; characterization, plot, and setting. As well as dismantling the text with Jacques Derrida’s theory Deconstruction, including; Differance (Delay or Differentiator), Trace, and Sous Rature (Crossmark). Then define this drama script with social relations or society. Based on the results of data analysis, the facts found in the story is chronological plot, the main character is the protagonist and Ratu Babangida as the antagonist character. Both of these characters as actors who have a big role in the course of the story. Based on deconstruction’s theory used, which there are all elements, namely differance in the setting of the first time the incident began , Sous Rature also occurs in the time setting because of the differance in dimensions that occur, then the introduction to the conflict that occurs. Cannot to described in reality , and revealed the Trace or absence of meaning to not leave or neglect to worship. Overall, the intrinsic elements of this research able to offer a space for human awareness not to leave obligation. Let alone neglect to worship. Absolutely the extrinsic explain how to describe a deconstruction theory through out in a drama script.